Carnitine palmitoyltransferase-II deficiency: case presentation and review of the literature - Mccormick Benjamin J.; Chirila Razvan M. (Sciendo, 2021)
Carnitine palmitoyltransferase-II deficiency, an autosomal recessive disorder, is the most common cause of recurrent rhabdomyolysis in adults. Recognition and avoidance of triggers, such as heavy exercise and stress, is key in prevention of further episodes; however, even with preventative measures, many patients will continue to experience periodic symptoms, including rhabdomyolysis. Avoidance of renal failure, correction of electrolyte disturbances and halting further muscle breakdown are the goals of treatment. It is essential for clinicians to recognize the signs and symptoms of acute disease in CPT-II deficiency. We present a case of recurrent rhabdomyolysis requiring hospitalization in a patient with CPT-II deficiency and review the literature for common clinical manifestations, diagnostics, and treatment strategies.